The Symbolic Meaning of Mak Ata and Pak Anon in Sukuraga Puppet - Salma, Meira Saprila (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2023)
This research aims to analyze the symbolism contained in the characters Mak Ata and Pak Anon in the Sukuraga puppet. Mak Ata is a wayang character that is depicted as a woman, while Pak Anon is a figure or character that is depicted as a man. In this study, we will analyze the symbolism of these two characters using a cultural and philosophical approach that involves the use of symbols such as their color, name, and physique. This research provides a deeper understanding of local policies, ethics, and values embedded in Indonesian culture by understanding and analyzing the symbolism of wayang characters such as Mak Ata and Pak Anon in the Sukuraga puppet.